Lanthanide(III) Complexes of DOTA-Glycoconjugates: A Potential New Class of Lectin-Mediated Medical Imaging Agents - André, João P. (2004)
The synthesis and characterization of a new class of DOTA (1,4,7,10-tetrakis(carboxymethyl)-1,4,7,10-tetraazacyclododecane) monoamide-linked glycoconjugates (glucose, lactose and galactose) of different valencies (mono, di and tetra) and their SmIII, EuIII and GdIII complexes are reported. The 1H NMR spectrum of EuIII-DOTALac2 shows the predominance of a single structural isomer of square antiprismatic geometry of the DOTA chelating moiety and fast rotation about the amide bond connected to the targeting glycodendrimer. The in vitro relaxivity of the GdIII-glycoconjugates was studied by 1H nuclear magnetic relaxation dispersion (NMRD), yielding parameters close to those reported for other DOTA monoamides. The known recognition of sugars by lectins makes these glycoconjugates good candidates for medical imaging agents (MRI and gamma scintigraphy).